Digitalisasi Pertanian: Akses Petani Terhadap Aplikasi Kartu Petani Berjaya (e-KPB) Di Provinsi Lampung, Indonesia - Dwi Wahyu Handayani; Yuni Ratna Sari; Lilih Muflihah (Jurnal Agregasi, 2026)
The Kartu Petani Berjaya (e-KPB) electronic application is an agricultural digitisation programme in Lampung Province that has been in place since 2020, designed to facilitate farmers’ access to their needs. In optimising the benefits of farmers’ resources, the structural and relational mechanisms governing the control of technology, capital, labour, knowledge and authority serve as mediators and determine the effectiveness of the e-KPB application. This qualitative study examines how access to the e-KPB application’s technology can optimise the benefits derived from farmers’ resources. The findings indicate that the e-KPB application, as an access control mechanism, structurally excludes some farmers in Lampung from accessing their essential needs (fertiliser, seeds, capital, guidance, technology, and marketing). Farmers face challenges in the reciprocal relationships between structural mechanisms in the use of the application, relating to acceptance, limitations in internet and electricity access, labour issues linked to educational levels, age, limitations in information and knowledge, and skills, as well as the government’s respect for farmers’ authority over their own resources. Nevertheless, there is a constellation of power among farmers, farmers’ groups and agricultural extension workers in controlling the opportunities for the beneficial use of these applications.